Extracellular Vesicle–Mediated Delivery of Circular RNA SCMH1 Promotes Functional Recovery in Rodent and Nonhuman Primate Ischemic Stroke Models. Issue 6 (11th August 2020) - Yang, Li; Han, Bing; Zhang, Zhiting; Wang, Shuguo; Bai, Ying; Zhang, Yuan; Tang, Ying; Du, Lingli; Xu, Ling; Wu, Fangfang; Zuo, Lei; Chen, Xufeng; et al.
Abstract : Background: Stroke is a leading cause of adult disability that can severely compromise the quality of life of patients, yet no effective medication currently exists to accelerate rehabilitation. A variety of circular RNA (circRNA) molecules are known to function in ischemic brain injury. Lentivirus-based expression systems have been widely used in basic studies of circRNAs, but safety issues with such delivery systems have limited exploration of the potential therapeutic roles for circRNAs. Methods: Circular RNA SCMH1 (circSCMH1) was screened from the plasma of patients with acute ischemic stroke by using circRNA microarrays. Engineered rabies virus glycoprotein-circSCMH1-extracellular vesicles were generated to selectively deliver circSCMH1 to the brain. Nissl staining was used to examine infarct size. Behavioral tasks were performed to evaluate motor functions in both rodent and nonhuman primate ischemic stroke models. Golgi staining and immunostaining were used to examine neuroplasticity and glial activation. Proteomic assays and RNA-sequencing data combined with transcriptional profiling were used to identify downstream targets of circSCMH1. Results: CircSCMH1 levels were significantly decreased in the plasma of patients with acute ischemic stroke, offering significant power in predicting stroke outcomes. The decreased levels of circSCMH1 were further confirmed in the plasma and peri-infarct cortex of photothrombotic stroke mice. Beyond demonstrating proof-of-concept for an RNA drug delivery technology, we observed that circSCMH1 treatment improved functional recovery after stroke in both mice and monkeys, and we discovered that circSCMH1 enhanced the neuronal plasticity and inhibited glial activation and peripheral immune cell infiltration. CircSCMH1 binds mechanistically to the transcription factor MeCP2 (methyl-CpG binding protein 2), thereby releasing repression of MeCP2 target gene transcription. Conclusions: Rabies virus glycoprotein-circSCMH1-extracellular vesicles afford protection by promoting functional recovery in the rodent and the nonhuman primate ischemic stroke models. Our study presents a potentially widely applicable nucleotide drug delivery technology and demonstrates the basic mechanism of how circRNAs can be therapeutically exploited to improve poststroke outcomes. Abstract : Supplemental Digital Content is available in the text.